Modeling and Deploying RESTful Services with SOMF-Based SOA: A Case Study in the Credit Guarantee Industry - Ramdhani, Amrid; Nilo Legowo (Ikatan Ahli Informatika Indonesia (IAII), 2025)
The integration of electronic systems across financial institutions poses significant challenges, particularly when legacy architectures rely on siloed, point-to-point connections. This often leads to what is commonly known as